DIAGNOSTIC VALUE OF ULTRASONOICALLY GUIDED FINE NEEDLE ASPIRATION BIOPSISES IN ABDOMINAL MASS LESIONS - Nihat OKÇU; M. Derya ONUK; Özkan ÜNAL; Ersin AKARSU; Lütfi İNCESU; Kenan AKGÖZ (Turkish Journal of Gastroenterology, 2020)
-